2011
DOI: 10.3389/fpsyg.2011.00202
|View full text |Cite
|
Sign up to set email alerts
|

Functional Hemispheric Specialization in Processing Phonemic and Prosodic Auditory Changes in Neonates

Abstract: This study focuses on the early cerebral base of speech perception by examining functional lateralization in neonates for processing segmental and suprasegmental features of speech. For this purpose, auditory evoked responses of full-term neonates to phonemic and prosodic contrasts were measured in their temporal area and part of the frontal and parietal areas using near-infrared spectroscopy (NIRS). Stimuli used here were phonemic contrast /itta/ and /itte/ and prosodic contrast of declarative and interrogati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
60
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(67 citation statements)
references
References 62 publications
(97 reference statements)
5
60
1
1
Order By: Relevance
“…Although the auditory cortex decodes fast acoustic modulations, relevant for the phonemic decoding within the speech flow in a bilateral way, the phonemic contrasts preferentially activate the left hemisphere of the temporal region in babies. The prosodic contrasts predominantly activated the right temporal region 10,15,21,22 . Reinforcing the role of this region for the sensory processing of emotional speech signals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the auditory cortex decodes fast acoustic modulations, relevant for the phonemic decoding within the speech flow in a bilateral way, the phonemic contrasts preferentially activate the left hemisphere of the temporal region in babies. The prosodic contrasts predominantly activated the right temporal region 10,15,21,22 . Reinforcing the role of this region for the sensory processing of emotional speech signals.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that the selected articles, which met the inclusion criteria of this study, are distributed in different In studies where only vocal sounds were used as stimulus, it can be observed that all the articles investigated the hemodynamic of the frontal and temporal regions, except 01 study 15 that investigated the parietal region in addition to these two areas. The brain hemodynamic responses were analyzed regarding the speech discrimination 16 , perception of phonological 16 and prosodic 15 contrasts, development of the hemispheric laterality for speech 15 and influence of the mother's voice in the speech recognition 17 .…”
Section: Figure 1 Flowchart Of the Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…However, adults have extensive experience with language, leaving open the issue of causation. Telkemeyer et al (2011), Arimitsu et al (2011), andMinagawa-Kawai et al (2011) now test these hypotheses on newborns and young infants using different temporally and spectrally modulated tone stimuli, asking whether the observed hemispheric specializations are the causes or the results of lateralized language processing. As an innovative extension of the research on early brain specialization for speech, Sato et al (2011) investigate whether, and if yes, how this specialization might be different in an atypical population, stuttering children and adults.…”
mentioning
confidence: 99%
“…May et al (2011) compare newborn infants' brain responses to the native language, spoken by the mother during pregnancy, and to an unknown language, in an attempt to investigate how prenatal experience with speech might shape the brain specialization for language. Telkemeyer et al (2011), Arimitsu et al (2011) as well as Minagawa-Kawai et al (2011) take a different approach, seeking to identify the acoustic, spectrotemporal properties of the speech signal might underlie brain specialization. In adults, it has been shown that fast-changing sounds or sounds modulated in time preferentially recruit areas in the left hemisphere that are part of the language network, while slowly changing sounds or sounds modulated spectrally tend to engage the right hemisphere (Zatorre et al, 2002;Hickok and Poeppel, 2007).…”
mentioning
confidence: 99%